Msme - Transforming Homemaker To Entrepreneur: Champions For Change - Vijayachandrika C.; Ayu Lestari (Al-Makki Publisher, 2023)
India has an equal number of males and females overall. But women are viewed unfavorably in this complicated modern society as second-class citizens or as men's property. Women are still behind and have not advanced to the maximum degree of utilization. The majority of governments make particular allowances for women's advancement, and they work hard to maximize the potential of women's skills. The specific services and facilities that are offered to women in the corporate world have not been fully used. There is a dearth of successful female business owners. The moment has come to educate the female population about the chances available to them to pursue their passions and give back to the community, which may contribute to the nation's speedy growth. MSMEs (Micro, Small, and Medium-Sized Enterprises) are crucial to a nation's economic growth. The entire planet has power. Through its many programs, the Ministry of MSMEs is empowering female entrepreneurs by assisting them in igniting their creativity and creating their own identities. In our current society, women are required to carry out economic activities and support their families wherever the cost of living rises. Now that attitudes in society have evolved, working women are no longer despised. An effort was made to research the position of women entrepreneurs in this report. Current problems experienced by female entrepreneurs. Additionally, it covers the assistance offered by MSMEs to female entrepreneurs.